Method for manufacturing a semi-transparent device suitable for thin film solar cells

CN115942850BActive Publication Date: 2026-10-13BEIHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211460298.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2026-10-13
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

[0005]本发明的目的为针对传统半透明电池的制备方法不适用于大面积工业化生产,且光透性和光电性能之间的平衡关系对活性层材料的限制,以及为实现透光效果而过度降低银电极厚度(10~25nm)引起的效率和操作稳定性的损失问题

Benefits of technology

[0031]互补的吸收是有机太阳能电池获得出色短路电流和功率转换效率的重要条件,却也是限制半透明器件透过率的关键因素,尤其是380~780nm波段的光利用,这无疑限制了光敏材料的选择和器件效率的提高。此外,对于目前主流的高性能三元体系,第三组分的加入会导致活性层薄膜消光系数的提升,为了保证器件具有足够的透光性就需要降低活性层薄膜的厚度,损失器件效率,也就是说,传统半透明器件的透过率和效率存在严重的互换关系。不仅如此,传统的半透明器件通过降低银电极厚度来实现透光的效果,但10nm左右的银电极极易在操作中损坏和变质,降低器件操作稳定性,不利于其商业化进程。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115942850B_ABST
    Figure CN115942850B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a semi-transparent device suitable for a thin film solar cell, and comprises the following steps: sequentially depositing hole transport, photoactive and electron transport materials on a clean ITO glass surface; using a special mask to deposit a silver grid as a top electrode, and the silver electrode covers a part of an effective photoelectric conversion area; then using etching solution or photoetching technology to process the device, and removing the active material outside the silver electrode coverage to make the area have high light transmittance; the method has the following advantages: the functional area division strategy breaks the balance between light transmittance and photoelectric performance in a traditional semi-transparent cell, and the limitation of materials, and enriches the selection of active materials; in addition, the device structure is not sensitive to the thickness and uniformity of the active layer and the silver electrode, and is more suitable for commercial large-area preparation; by adjusting the specifications of the silver grid, the transmittance of the device can be simply and accurately regulated, various application requirements can be met, and the application value of the semi-transparent device is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell fabrication technology, and more specifically, to a method for fabricating semi-transparent devices suitable for thin-film solar cells. Background Technology

[0002] Polymer solar cells (OSCs), as a star product in third-generation photovoltaic technology, possess unique advantages such as flexible fabrication, light weight, and good light transmittance, enabling them to meet a wider range of application scenarios and demonstrating great development potential. Compared to other solar cells, organic solar cells are composed of carbon-based organic material systems, exhibiting green, environmentally friendly, and low-pollution characteristics. Furthermore, these materials are flexible and bend-resistant, showing great application potential in areas such as electronic skin and wearable devices. The flexibility, versatility, and chemical modification capabilities of organic materials facilitate targeted and controllable adjustment of device performance by researchers. Currently, the energy conversion efficiency of single-junction rigid devices has exceeded 19%, while tandem devices have reached over 20%.

[0003] Compared to other systems, organic materials possess unique advantages in terms of translucency. Translucent organic solar cells (ST-OSCs) can be fabricated into car windows, building roofs, and exterior walls, playing a crucial role in building-integrated photovoltaics and smart electronic windows. Transparent devices not only beautify building appearances but can also directly convert sunlight into electricity, powering building interiors and mobile devices. Currently, fullerene acceptor-based translucent devices have an average visible light transmittance (AVT) of 20–30% and a power conversion efficiency of only 4–8%. However, with the advent of non-fullerene acceptors, translucent devices can achieve conversion efficiencies of 8–15% at 20–40% transmittance, significantly advancing the commercialization of translucent devices. However, current research faces several challenges: limitations to small-area fabrication; a severe trade-off between light transmittance and absorption in traditional translucent cells restricts further efficiency improvements; and the overall light transmittance of the device is highly sensitive and closely related to the thickness of the active layer and silver electrode, hindering large-scale production control. Furthermore, excessively thin metal electrodes can lead to poor charge transport performance and operational stability. Therefore, developing new device structures and electrode fabrication strategies is essential for the commercialization of ST-OSCs.

[0004] To address the unfavorable trade-off between device efficiency and transmittance in traditional semi-transparent solar cells, and the loss of efficiency and operational stability caused by excessively reducing the thickness of the silver electrode (10–25 nm) to achieve light transmission, a method for fabricating semi-transparent devices suitable for thin-film solar cells is proposed. Summary of the Invention

[0005] The purpose of this invention is to address the problems that traditional methods for preparing semi-transparent batteries are not suitable for large-area industrial production, the limitations imposed on the active layer material by the balance between light transmittance and photoelectric performance, and the loss of efficiency and operational stability caused by excessively reducing the thickness of the silver electrode (10-25 nm) to achieve light transmittance.

[0006] In view of this, a first aspect of the present invention is to provide a method for fabricating a semi-transparent device suitable for thin-film solar cells.

[0007] A second aspect of the present invention is to provide a semi-transparent device.

[0008] The first aspect of the present invention provides a method for fabricating a semi-transparent device suitable for thin-film solar cells, comprising the following steps: S1, ultrasonically cleaning ITO glass for 20 minutes sequentially with acetone, detergent, distilled water, and isopropanol; then completely drying the ITO glass in an oven, followed by air plasma treatment for 2 minutes; S2, spin-coating hole transport material PEDOT:PSS onto the surface of the ITO glass to form a thin film with a thickness of 35 nm to 40 nm, followed by thermal annealing in air; S3, depositing an active layer onto the surface of PEDOT:PSS in a glove box under nitrogen atmosphere, followed by annealing; S4, performing an air cooling treatment, dissolving PNDIT-F3N in methanol and acetic acid to prepare a solution, and then spin-coating it onto the active layer to form an electron transport layer; S5, in a 3 × 10⁻⁶ m² / h⁻¹ glove box... -4 In a high vacuum environment of Pa, a silver mesh with a thickness of 100nm to 120nm is deposited on the electron transport layer using a mask as the top electrode to obtain a semi-transparent device preform; S6, an etching solution is selected to treat the semi-transparent device preform prepared in step S5 to remove the active layer in the area without silver electrode coverage, thus completing the fabrication of the semi-transparent device.

[0009] The present invention provides a method for fabricating a semi-transparent device suitable for thin-film solar cells. In this method, ITO glass is first ultrasonically cleaned sequentially with four liquids for 20 minutes each time, followed by drying and air plasma treatment. Then, hole transport material PEDOT:PSS is spin-coated onto the ITO glass surface until a thin film with a thickness of 35nm–40nm is formed, followed by thermal annealing. An active layer is deposited on the PEDOT:PSS surface in a nitrogen atmosphere in a glove box, followed by annealing. PNDIT-F3N is first dissolved in methanol and acetic acid to prepare a solution, which is then spin-coated onto the surface of the active layer to form an electron transport layer. The process is repeated at 3×10⁻⁶. -4In a high vacuum environment of Pa, a silver mesh is deposited on the surface of the electron transport layer using a mask to complete the setting of the top electrode, thus completing the overall structure laying and fabrication of the semi-transparent device. The fabricated semi-transparent device is then cleaned with an etching solution or subjected to photolithography to remove the active layer in areas not covered by the silver mesh electrode, so that the active layer has the same through holes as the silver mesh. This operation can improve the overall light transmittance of the device.

[0010] Furthermore, in step S6, photolithography is used as an alternative means of cleaning the semi-transparent device preform prepared in step S5 using an etching solution.

[0011] In addition, the technical solutions provided by embodiments of the present invention may also have the following additional technical features:

[0012] In any of the above technical solutions, the temperature of the thermal annealing treatment in step S2 is 150°C and the time is 20 min.

[0013] In this technical solution, the temperature and time of thermal annealing are controlled so that the hole transport material PEDOT:PSS spin-coated on the surface of ITO glass crystallizes into a flat film, thereby stabilizing the various process parameters after spin-coating.

[0014] In any of the above technical solutions, the spin coating speed range in steps S2 and S4 is 4000-4200 rpm.

[0015] In this technical solution, the spin coating speed is controlled within the range of 4000-4200 rpm, which ensures stable adhesion of the material and uniform and appropriate surface thickness after processing.

[0016] In any of the above technical solutions, the concentration of the solution formed by dissolving PNDIT-F3N in methanol and acetic acid in S4 is 1.2 to 1.3 mg / mL; and / or the volume ratio of methanol to acetic acid in the solution of S4 is 99.5:0.5.

[0017] In this technical solution, by limiting the concentration of PNDIT-F3N in the solution and further controlling the film thickness within the range of 4 to 6 nm, the actual effect after processing is ensured.

[0018] In any of the above technical solutions, the active layer includes one or more of the following films: polymer donor-acceptor blend film, polymer / small molecule blend film, small molecule donor-acceptor blend film, perovskite film, and dye-sensitized material film.

[0019] In this technical solution, the processing method of S1-S6 increases the range of selectable active layers, specifically polymer donor-acceptor blend films, polymer / small molecule blend films, small molecule donor-acceptor blend films, perovskite films, and dye-sensitized material films, which can adapt to various different material applications.

[0020] In any of the above technical solutions, the etching solution is a solution containing one or more of the following substances: chloroform, chlorobenzene, toluene, o-dichlorobenzene, and o-xylene.

[0021] In this technical solution, the etching solution is selected from one or more raw materials such as chloroform, chlorobenzene, toluene, o-dichlorobenzene and o-xylene to clean the active layer of different materials, ensuring that cleaning can be carried out when facing different active layers.

[0022] In any of the above technical solutions, the maximum transmittance of the semi-transparent device is higher than 90%.

[0023] In this technical solution, the silver mesh can be designed according to the actual needs of use, and then the light transmittance is adjusted by the cleaning effect of the etching solution, so as to achieve the purpose of controlling the photoelectric conversion efficiency and transmittance.

[0024] A second aspect of the present invention is to provide a semi-transparent device, the semi-transparent device having a multi-layer stacked structure, comprising, from bottom to top: ITO glass, hole transport material, active layer, electron transport layer, and silver mesh; wherein the active layer is provided with through holes that longitudinally correspond to the holes in the silver mesh.

[0025] The second aspect of the present invention provides a semi-transparent device. The final product of the method of the present invention is a semi-transparent device, which adopts a stacked structure of ITO glass, hole transport material, active layer, electron transport layer and silver grid in sequence from bottom to top, and the through-holes of the active layer correspond to the holes of the silver grid through the cleaning action of the etching solution.

[0026] In any of the above technical solutions, the semi-transparent device is divided into a light converter with the silver grid and a light transmitter without the silver grid along the stacking direction of the structure, and a plurality of the light transmitters are arranged laterally at intervals inside the semi-transparent device, so that the semi-transparent device can improve its photoelectric performance without being constrained by light transmittance.

[0027] In this technical solution, the complete semi-transparent device is divided into a light converter in the silver-covered area and a light transmitter in the silver-uncovered area. Therefore, the selection of the active layer can focus only on high photoelectric performance, without having to consider its light transmittance, nor the balance between photoelectric performance and light transmittance. This makes the selection of active layer materials more diversified.

[0028] Furthermore, the light converter is a mesh structure with holes arranged along its internal stacking direction, and multiple through holes in the mesh structure are equipped with light-transmitting elements. Compared to traditional semi-transparent devices, this functional area separation strategy makes the device performance insensitive to the material selection and thickness of the active layer and top electrode, exhibiting higher process tolerance and suitability for large-area industrial production. In addition, extending this mesh structure to the application of flexible photovoltaics can effectively release mechanical stress and improve the overall bending durability of the device.

[0029] Specifically, the light converter includes ITO glass, hole transport material, active layer, electron transport layer, and silver mesh, and the light transmitter includes ITO glass and hole transport material.

[0030] The beneficial effects of this invention compared to the prior art are as follows:

[0031] Complementary absorption is crucial for organic solar cells to achieve excellent short-circuit current and power conversion efficiency, but it is also a key factor limiting the transmittance of semi-transparent devices, especially in the 380–780 nm wavelength range. This undoubtedly restricts the selection of photosensitive materials and the improvement of device efficiency. Furthermore, for the currently mainstream high-performance ternary systems, the addition of a third component leads to an increase in the extinction coefficient of the active layer film. To ensure sufficient light transmittance, the thickness of the active layer film needs to be reduced, resulting in a loss of device efficiency. In other words, there is a serious trade-off between transmittance and efficiency in traditional semi-transparent devices. Moreover, traditional semi-transparent devices achieve light transmission by reducing the thickness of the silver electrode, but silver electrodes around 10 nm are highly susceptible to damage and deterioration during operation, reducing device operational stability and hindering its commercialization.

[0032] This invention relates to a novel semi-transparent device based on a mesh electrode, which utilizes an etching solution to clean and remove the active layer in areas without silver electrodes to achieve light transmission. The operation is simple; the semi-transparent device is divided into a light converter with a silver mesh-covered area and a light transmitter without the silver mesh, avoiding the dilemma of balancing light absorption and light transmission in the active layer material. Therefore, it is applicable to various photosensitive materials, without needing to consider film thickness and extinction coefficient. Furthermore, the proportion of each functional area can be adjusted as needed to meet various application requirements, thereby effectively improving the efficiency and application value of the semi-transparent device.

[0033] The use of silver mesh electrodes breaks the limitations imposed on active layer materials by the traditional balance between light transmittance and photoelectric performance in semi-transparent batteries, thus enriching the selection of active layer materials. Furthermore, by adjusting the specifications of the silver mesh electrodes, the transmittance of the device can be easily and precisely controlled to meet various application requirements.

[0034] Additional aspects and advantages of embodiments of the invention will become apparent in the following description or may be learned by practice of embodiments of the invention. Attached Figure Description

[0035] The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of the invention.

[0036] Figure 1 This is a schematic diagram of a semi-transparent organic solar cell based on a forward structure according to the present invention;

[0037] Figure 2 Optical photographs of the semi-transparent devices based on silver mesh electrodes of different specifications according to the present invention;

[0038] Figure 3 Comparison of optical photographs of the semi-transparent device based on metal mesh electrodes prepared in Example 1 of the present invention before and after etching solution treatment;

[0039] Figure 4 Comparison of optical photographs of a semi-transparent device based on a metal mesh electrode prepared in Example 1 of the present invention and a conventional semi-transparent device;

[0040] Figure 5 A comparison of the light transmittance of a semi-transparent device based on a metal mesh electrode prepared in Example 1 of the present invention and a conventional semi-transparent device;

[0041] Figure 6 This is a statistical analysis of the residual device efficiency after treatment with different etching solutions in Example 1 of the present invention;

[0042] Figure 7 The transmission spectra of the silver-free electrode-covered portion and the ITO / PEDOT:PSS substrate after etching treatment according to the present invention are shown. Detailed Implementation

[0043] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other.

[0044] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and therefore the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0045] Please see Figure 1-7 The first aspect of the present invention provides a method for fabricating a semi-transparent device suitable for thin-film solar cells, comprising the following steps:

[0046] S1. The ITO glass was ultrasonically cleaned for 20 minutes with acetone, detergent, distilled water and isopropanol respectively. After the ITO glass was completely dried in the oven, it was subjected to air plasma treatment for 2 minutes.

[0047] S2, hole transport material PEDOT:PSS was spin-coated onto the ITO surface at a speed of 4000 rpm to a thickness of 35-40 nm, and then heat-annealed in air at 150°C for 20 min.

[0048] S3, the active layer is deposited on the PEDOT:PSS surface in a glove box under nitrogen atmosphere and then annealed.

[0049] S4, after cooling, PNDIT-F3N, 1.2-1.3 mg / mL electron transport layer dissolved in methanol and acetic acid, is spin-coated onto the active layer at a speed of 4200 rpm;

[0050] S5, at a high vacuum of 3×10 -4 Under Pa, a silver mesh with a thickness of 100-120 nm is deposited on the electron transport layer formed by S4 using a special mask as the top electrode, thus completing the initial fabrication of the device;

[0051] S6. Select an etching solution to clean the complete device prepared in S5, in order to remove the active layer in the area without silver electrode coverage and improve the light transmittance of the overall device. This completes the final preparation of the semi-transparent device.

[0052] Photosensitive layer materials include polymer donor-acceptor blend films, polymer / small molecule blend films, small molecule donor-acceptor blend films, perovskite films, and dye-sensitized materials, which can be prepared by spin coating, blade coating, roll-to-roll printing, groove deposition, and dual-groove printing.

[0053] The silver grid allows for adjustment of electrode specifications to meet specific needs, thereby regulating photoelectric conversion efficiency and transmittance, with a maximum transmittance exceeding 90%.

[0054] The etching solution is selected from one or more of the following substances: chloroform, chlorobenzene, toluene, o-dichlorobenzene, o-xylene; auxiliary solvent: methanol.

[0055] Example 1

[0056] To test the performance of the silver mesh top electrode and the overall device transmittance in this invention, the following experiments were conducted using the controlled variable method. The specific steps are as follows:

[0057] The PEDOT:PSS hole transport layer, active layer and PNDIT-F3N electron transport layer were deposited on a clean ITO bottom electrode surface. During the process, the solution concentration, spin coating speed and time, annealing temperature and time need to be kept constant to ensure that the difference in experimental results depends entirely on the difference in the top electrode.

[0058] Different mask specifications are selected according to actual needs to prepare the top electrode on the substrate by evaporation and preliminary efficiency testing. Then, one or more etching solvents are selected from solvents such as chloroform, chlorobenzene, toluene, o-dichlorobenzene, and o-xylene, and combined with orthogonal solvents for post-processing to remove the active layer in the area without silver electrode coverage in order to improve the overall light transmittance of the device.

[0059] Transmission spectroscopy was performed on the exposed substrate after etching solution treatment. The actual transmittance of the final device was calculated based on the average light transmittance formula and the theoretical light transmittance formula. The power conversion efficiency of the device was then characterized.

[0060] The sample prepared in this embodiment was photographed using optical imaging techniques and characterized by a testing instrument. The results are as follows:

[0061] (1) Figure 3 Optical photographs of the semi-transparent device in this invention before and after treatment with an etching solution are shown, revealing that the use of the etching solution can significantly improve the light transmittance of the battery.

[0062] (2) Figure 4 and Figure 5 The accompanying photographs show a comparison between the semi-transparent device of this invention and a conventional semi-transparent device. The formula for calculating transmittance in a conventional semi-transparent battery is also provided.

[0063]

[0064] Where T is the transmission spectrum, F is the incident light flux, and E is the human eye photon response.

[0065] The formula for calculating the theoretical transmittance of the semi-transparent battery in this invention is as follows:

[0066]

[0067] Where A1 and S1 represent the average light transmittance and area of ​​the silver-free electrode region after etching solution treatment, respectively; S represents the effective cell area. Figure 4 On the right, the effective area of ​​a traditional semi-transparent device is 5.12 mm². 2 ; Figure 4 On the left, the effective area of ​​the new semi-transparent device is 140mm². 2 The effective area is increased by at least 26 times, proving that this strategy is suitable for the fabrication of large-area devices. Figure 5On the right, the new semi-transparent device exhibits superior light transmittance, which is of great significance for promoting the large-scale application of semi-transparent devices.

[0068] (3) Figure 6 The efficiency retention distribution of the devices was compared when chloroform, toluene, chlorobenzene, o-xylene, and o-dichlorobenzene were used as etching solutions. It was found that treatment with toluene minimized the erosion of the active layer covered by the silver electrode by the etching solution, effectively improving efficiency retention.

[0069] (4) Figure 7 The transmission spectra of the silver-free electrode-covered portion after etching and the ITO / PEDOT:PSS substrate were shown. It was found that the use of chloroform and toluene can almost completely remove the active layer, which is crucial for the device to obtain high light transmittance.

[0070] Example 2

[0071] To investigate the device performance and overall transmittance of the silver grid top electrode in this invention when applied to perovskite solar cells, the following experiments were conducted using the controlled variable method. The specific steps are as follows:

[0072] The PEDOT:PSS hole transport layer, perovskite photosensitive layer, PCBM electron transport layer, and BCP modification layer were deposited on a clean ITO bottom electrode surface. During the process, it is necessary to maintain a constant solution concentration, spin coating speed and time, timing of adding antisolvent (chlorobenzene / toluene, etc.), and annealing temperature and time to ensure that the differences in experimental results depend as much as possible on the differences in the top electrode.

[0073] Different mask specifications are selected according to actual needs to prepare the top electrode of the substrate by evaporation, and preliminary efficiency tests are performed. Photolithography is used to remove the perovskite layer in the areas without silver electrode coverage to improve the overall light transmittance of the device.

[0074] Transmission spectroscopy was performed on the exposed substrate after photolithography. The actual transmittance of the final device was calculated based on the average light transmittance formula and the theoretical light transmittance formula. The power conversion efficiency of the device was then characterized.

[0075] In the description of this invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this invention, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.

[0076] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for fabricating a semi-transparent device suitable for thin-film solar cells, characterized in that, Includes the following steps: S1, the ITO glass was ultrasonically cleaned for 20 minutes in sequence with acetone, detergent, distilled water and isopropanol; then the ITO glass was completely dried in an oven and then subjected to air plasma treatment for 2 minutes. S2, hole transport material PEDOT:PSS is spin-coated onto the surface of ITO glass to form a thin film with a thickness of 35-40 nm, and then subjected to thermal annealing in air. S3, the active layer is deposited on the PEDOT:PSS surface in a glove box under nitrogen atmosphere and then annealed. S4. Perform an idle cooling process, dissolve PNDIT-F3N in methanol and acetic acid to prepare a solution, and then spin-coat it onto the active layer to form an electron transport layer. S5, in 3×10 -4 In a high vacuum environment of Pa, a silver mesh with a thickness of 100-120 nm is deposited on the electron transport layer using a mask as the top electrode to obtain a semi-transparent device preform; S6. Select an etching solution to process the semi-transparent device preform prepared in step S5, remove the active layer in the area without silver electrode coverage, and complete the fabrication of the semi-transparent device.

2. The method for fabricating a semi-transparent device suitable for thin-film solar cells according to claim 1, characterized in that, The temperature of the heat annealing process in step S2 is 150°C and the time is 20 minutes.

3. The method for fabricating a semi-transparent device suitable for thin-film solar cells according to claim 1, characterized in that, The spin coating speed range in steps S2 and S4 is 4000-4200 rpm.

4. The method for fabricating a semi-transparent device suitable for thin-film solar cells according to claim 1, characterized in that, In step S4, the concentration of the solution formed by dissolving PNDIT-F3N in methanol and acetic acid is 1.2–1.3 mg / mL; and / or The volume ratio of methanol to acetic acid in the S4 solution is 99.5:0.

5.

5. The method for fabricating a semi-transparent device suitable for thin-film solar cells according to claim 1, characterized in that, The active layer includes one or more of the following membranes: polymer donor-acceptor blend membrane, polymer / small molecule blend membrane, small molecule donor-acceptor blend membrane, perovskite film, and dye-sensitized material film.

6. The method for fabricating a semi-transparent device suitable for thin-film solar cells according to claim 1, characterized in that, The etching solution is a solution containing one or more of the following substances: chloroform, chlorobenzene, toluene, o-dichlorobenzene, and o-xylene.

7. The method for fabricating a semi-transparent device suitable for thin-film solar cells according to claim 1, characterized in that, The maximum transmittance of the semi-transparent device is higher than 90%.

8. The translucent device obtained by the preparation method according to any one of claims 1-7, characterized in that, The semi-transparent device has a multi-layer stacked structure, consisting of, from bottom to top: ITO glass, hole transport material, active layer, electron transport layer, and silver mesh; The active layer is provided with through holes that correspond longitudinally to the holes in the silver mesh.

9. The semi-transparent device according to claim 8, characterized in that, The semi-transparent device is divided into a light converter with the silver grid and a light transmitter without the silver grid along the stacking direction of the structure, and a plurality of the light transmitters are arranged laterally at intervals inside the semi-transparent device, so that the photoelectric performance of the semi-transparent device is improved without being constrained by the light transmittance.

Citation Information

Patent Citations

  • Process for ensuring surface etching uniformity of front panel glass of amorphous silicon battery

    CN102336525A

  • Flexible solar cell

    CN106206955A